A Practical Guide to Digital Forensics Investigations - Hayes, Darren Richard (Pearson, 2021)
As digital crime soars, so does the need for experts who can recover and evaluate evidence for successful prosecution. Now, Dr. Darren Hayes has thoroughly updated his definitive guide to digital forensics investigations, reflecting current best practices for securely seizing, extracting and analysing digital evidence, protecting the integrity of the chain of custody, effectively documenting investigations, and scrupulously adhering to the law, so that your evidence is admissible in court. Every chapter of this new 2nd edition is revised to reflect newer technologies, the latest challenges, technical solutions, and recent court decisions. Hayes has added detailed coverage of wearable technologies, IoT forensics, 5G communications, vehicle forensics, and mobile app examinations; advances in incident response; and new iPhone and Android device examination techniques. Through practical activities, realistic examples, and fascinating case studies, you'll build hands-on mastery and prepare to succeed in one of todays fastest-growing fields